Decomposition Formulas for Triple q-Hypergeometric Functions. (15th May 2014) - Ernst, Thomas
Abstract : In the spirit of Hasanov, Srivastava, and Turaev (2006), we introduce new inverse operators together with a more general operator and find a summation formula for the last one. Based on these operators and the earlier known q -analogues of the Burchnall-Chaundy operators, we find 15 symbolic operator formulas. Then, 10 expansions for the q -analogues of Srivastava's three triple hypergeometric functions in terms of ϕ 3 4 q -hypergeometric and q -Kampé de Fériet functions are derived. These expansions readily reduce to 10 new expansions for the three triple Srivastava hypergeometric functions in terms of F 3 4 hypergeometric and Kampé de Fériet functions.